The Effect of Self-Monitoring on Mental Effort and Problem-Solving Performance: A Mixed-Methods Study - Madison Graham; Marinela Ilic; Martine Baars; Kim Ouwehand; Fred Paas (MDPI AG, 2024)
Self-regulated learning (SRL) has become increasingly important for learners in the 21st century as they engage more frequently in student-centered education. Accurate self-monitoring of one's learning process is central to SRL. However, research has shown that learners often struggle with monitoring accuracy. One possible explanation is that the process of self-monitoring itself may add cognitive load, potentially reducing both self-monitoring accuracy and overall performance. In the current study, we investigated the effects of self-monitoring on perceived mental effort and performance during problem-solving tasks of increasing complexity. Participants in the experimental condition were instructed to think aloud while problem-solving, while those in the control condition did not receive such instructions. Our findings indicate no interaction effect between the requirement for explicit and continuous self-monitoring and task complexity on perceived mental effort and performance. However, task complexity significantly impacted the perceived mental effort and performance in both conditions, while it affected monitoring accuracy exclusively in the experimental condition. Furthermore, qualitative analyses showed that the participants in the experimental conditions engaged in self-monitoring during 21.2 % of their think-aloud protocols. Contrary to previous research, self-monitoring did not appear to increase cognitive load, although the experimental participants took significantly longer to complete all the tasks. Possible explanations for these findings are discussed.